Molecular genotyping and subtyping of Clostridium perfringens isolated from fatal enterotoxemia in alpacas - Pérez, David (2012)
Although enterotoxemia produced by Clostridium perfringens causes elevated neonatal mortality in the alpaca, scarce information exists on the virulence factors (toxins) which play an important role in the pathogenesis of the disease. The objective of this study was to genotype and subtype C. perfringens isolates from enterotoxemia induced mortalities based on the presence of genes cpa, cpb, etx and iap which encode the toxins α, β, g, and , and the genes cpe and cpb2 which encode the enterotoxin (cpe) and β2-toxins, respectively. A total of 47 C. perfringens isolates were obtained from the small intestine of neonatal alpaca mortalities which presented clinical signs, as well as gross and histological injuries typical of enterotoxemia. The results showed that 46/47 (97.9%) of the isolates were genotype A, 13 of these 46 (28.3%) also had cpb2 (genotype A, subtype cpe-cpb2+), while the remaining 33 (71.3%) were negative for both cpe and cpb2 genes (genotype A, subtype cpe-cpb2 -) and only 1/47 (2.1%) had the cpa, cpb y cpe genes (genotype C, subtype cpe+cpb2-). The results indicate that both the alpha and beta2 toxins likely play an important role in enterotoxemia aetiology, but excluded participation of the enterotoxin.